Microstrip antenna system for communication capabilities applications - Fredelino A. Galleto Jr.; Aaron Don M. Africa; Alyssa Joie F. Tablada; John Ernesto G. Amadora Jr.; Ira Third L. Burgos; Alliyah Mae K. Borebor; Rocelle Andrea S. Belandres; Rafael Dominic L. Montaño (Institute of Advanced Engineering and Science, 2024)
In this comparative study, seven different microstrip antenna shapes, including rectangular, elliptical, triangular, inset fed, H-notch, and E-notch, were observed and analyzed, focusing on their suitability for global positioning system (GPS) application in microsatellites. To enable meaningful comparison, the study utilized the optimal resonant frequency in GPS applications, which is 1.57542 GHz. All the antenna designs have been generated using MATLAB’s Antenna Toolbox and are 100% efficient under ideal conditions with zero polarization loss, which is assumed in the link budget analysis. The results show that each antenna shape has been found to offer distinct advantages and limitations. Along with this, the circular and elliptical patch antenna presented a well-balanced performance, which is suitable for GPS applications. However, the elliptical shape falls behind the circular shape, which was determined to be the most optimal choice for GPS application, providing excellent isotropic antenna gain, return loss, voltage standing wave ratio (VSWR), and strong link budget analysis results.